Corneal wasp sting: A case report and review of literature - Mohammad Hossein Nowroozzadeh; Adel Hamid; Alireza Bolkheir; Mohammad Shirvani; Mehrnoosh Maalhagh (Journal of Current Ophthalmology, 2019)
Purpose: To report severe immunologic and toxic reaction due to corneal wasp sting that may cause catastrophic sight-threatening outcomes. Methods: A 45-year-old man referred to the emergency room with corneal wasp sting of Vespa Orientalis. The authors review previous Medline literature about this topic. Results: In our case, the response to frequent topical corticosteroid was dramatic, and at the seventh day after injury, all inflammatory responses in the anterior segment of the eye had been resolved. Conclusion: Corneal wasp injury with Vespa Orientalis can cause severe inflammation of the cornea and the anterior segment. Topical corticosteroids are the mainstay of treatment. Keywords: Wasp, Sting, Cornea